A mechanoelectrical mechanism for detection of sound envelopes in the hearing organ. Issue 1 (December 2018) - Nuttall, Alfred; Ricci, Anthony; Burwood, George; Harte, James; Stenfelt, Stefan; Cayé-Thomasen, Per; Ren, Tianying; Ramamoorthy, Sripriya; Zhang, Yuan; Wilson, Teresa; Lunner, Thomas; Moore, Brian; et al.
Abstract To understand speech, the slowly varying outline, or envelope, of the acoustic stimulus is used to distinguish words. A small amount of information about the envelope is sufficient for speech recognition, but the mechanism used by the auditory system to extract the envelope is not known. Several different theories have been proposed, including envelope detection by auditory nerve dendrites as well as various mechanisms involving the sensory hair cells. We used recordings from human and animal inner ears to show that the dominant mechanism for envelope detection is distortion introduced by mechanoelectrical transduction channels. This electrical distortion, which is not apparent in the sound-evoked vibrations of the basilar membrane, tracks the envelope, excites the auditory nerve, and transmits information about the shape of the envelope to the brain. The sound envelope is important for speech perception. Here, the authors look at mechanisms by which the sound envelope is encoded, finding that it arises from distortion produced by mechanoelectrical transduction channels. Surprisingly, the envelope is not present in basilar membrane vibrations.